Parametric Study of an Earth-Air Heat Exchanger Assisted by a Green Wall for Passive Cooling in Hot Climates - Djamel Belatrache; Saïd Bentouba; Mahmoud Bourouis (Global Journal of Earth Science and Engineering, 2019)
Cooling of buildings during summers in hot climates is an important issue for architects and builders and in terms of energy consumption, residential and tertiary buildings are among the highest consumers. This paper presents a numerical study, focused on a new design for a passive cooling system that uses an earth-air heat exchanger (EAHE), which was assisted by a green wall/air heat exchanger (GAHE) in hot climatic conditions. The tubes buried in the ground and the shadow of a vertical green wall offer considerable advantages for saving energy. The depth of the pipes in the ground was calculated by taking into account the physical properties of the soil. A parametric study was carried out by taking into account the pipe diameter, pipe length, pipe depth in the ground, and the velocity of air in the pipes. The vertical pipe in the green wall allowed a significant additional drop in the air temperature at low air velocities or small pipe depths in the ground. This means that shorter pipe lengths can be used in the earth-air heat exchanger to keep the air outlet temperature of the same order. For an earth air heat exchanger assisted by a green wall operating in hot climates, the design and operation parameters recommended are; pipe diameter 120 mm, length of the buried pipe 4 m, depth in the ground 30 m and air velocity 1 m/s.